Седьмая профессия Маши Филипенко - Успенский Эдуард Николаевич (Библиотека школьника, 2000)
Экземпляры: ф.1 (2000) / Инвентарный номер: 42534 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 77 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4